2015
DOI: 10.4236/health.2015.712173
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Revised Moderate Drinking Program for Enhancing Behavior Modification in the Workplace for Heavy Drinkers: A Randomized Controlled Trial in Japan

Abstract: This study examined the effects of the Hizen Alcoholism Prevention Program (HAPPY) and the revised version of HAPPY (HAPPY Plus), and also compared the two programs to determine whether the HAPPY Plus achieved better outcomes for heavy drinkers in the workplace. The HAPPY Plus designed to strengthen participants' recruitment, perception of threat, stress management, behavior modification by self-monitoring using a calendar-based diary, and to prevent dropout by telephone and e-mail follow-up by a trained nurse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…Risk thresholds in these targeted studies included hazardous or harmful drinking ( n = 10), cardiovascular disease (CVD) risk ( n = 1), and having accessed an Employee Assistance Program (EAP) for mental health or alcohol and/or other drug use ( n = 3). Of the 10 interventions delivered to workers who drank at hazardous or harmful levels, three excluded participants if they met criteria for alcohol dependence ( 41 , 43 , 49 ). Broad health promotion interventions were most common ( n = 9), followed by brief interventions (BIs; n = 7), psychosocial interventions ( n = 7), e-health interventions ( n = 4), EAPs ( n = 3), drug testing ( n = 2), and stepped care ( n = 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Risk thresholds in these targeted studies included hazardous or harmful drinking ( n = 10), cardiovascular disease (CVD) risk ( n = 1), and having accessed an Employee Assistance Program (EAP) for mental health or alcohol and/or other drug use ( n = 3). Of the 10 interventions delivered to workers who drank at hazardous or harmful levels, three excluded participants if they met criteria for alcohol dependence ( 41 , 43 , 49 ). Broad health promotion interventions were most common ( n = 9), followed by brief interventions (BIs; n = 7), psychosocial interventions ( n = 7), e-health interventions ( n = 4), EAPs ( n = 3), drug testing ( n = 2), and stepped care ( n = 1).…”
Section: Resultsmentioning
confidence: 99%
“…Harada et al ( 41 ) conducted the only evaluation of a targeted psychosocial intervention for high-risk (but not dependent) drinkers in white-collar Japanese workplaces. They evaluated the “Haizen Alcoholism Prevention Program” (HAPPY) against a modified version (“HAPPY Plus”).…”
Section: Resultsmentioning
confidence: 99%
“…If a short (5‐min) intervention or single‐point intervention shows sufficient effect, there may be certain advantages in the implementation of SBI under time constraints in daily clinical practice. Second, although studies have indicated that the occupational healthcare system in Japan makes the workplace an important site for SBI, results regarding effectiveness have been inconsistent (Araki et al, 2006; Harada et al, 2015; Ito et al, 2015; Iyadomi et al, 2013). Lack of initial screening may lead to the failure to intervene in the target population adequately.…”
Section: Introductionmentioning
confidence: 99%